Neurofeedback technique for treating male schizophrenia patients with impulsive behavior: a randomized controlled study - Li, Zhenkuo; Ren, Hao; Tian, Yinghan; Zhou, Jiqian; Chen, Wenhao; OuYang, Guohua; Chen, Zhaolai; Yi, Wei; Song, Hongli; Xie, Peng; Wang, Xinchun; Chen, Xi; et al. (Frontiers in Psychiatry, 2024)
Background: Schizophrenia is one of the most severe mental disorders, frequently associated with aggression and violence, particularly in male patients. The underlying mechanisms of violent behavior in these patients remain unclear, limiting effective treatment options and highlighting the need for further research into interventions for impulsive behaviors. This study aims to evaluate the clinical efficacy of neurofeedback treatment in hospitalized male schizophrenia patients exhibiting impulsive behaviors.The study was designed as a single-center, randomized, single-blind, shamcontrolled parallel trial. Eighty patients were randomly assigned to either a study group or a control group. The control group received risperidone and sham neurofeedback, while the study group received risperidone and active neurofeedback therapy. Both groups underwent training five times per week, with each session lasting 20 minutes, over a six-week period. Clinical symptoms were assessed at baseline, three weeks and six weeks using the Positive and Negative Syndrome Scale (PANSS), the Modified Overt Aggression Scale (MOAS), and the Rating Scale for Extrapyramidal Side Effects (RSESE). Statistical analyses were conducted to compare the therapeutic effects between the two groups at the study's conclusion.Results: Initial comparisons showed no significant differences in baseline data, except for the number of prior hospitalizations (P<0.018). By the end of the study, the study group demonstrate significant improvements in MOAS and PANSS scores (including 删除了: among